Error Patterns in Eleventh-Grade Students’ Descriptive Texts Using Surface Strategy Taxonomy - Nisrina Nafisa Putri Muzakar; Sri Widodo; Abdul Ngafif; Ploychompoo Hankamolsiri (Universitas Islam Negeri Palopo, 2026)
This study aimed to identify the types of errors found in eleventh-grade students’ descriptive texts at SMK Muhammadiyah Purworejo by applying the Surface Strategy Taxonomy proposed by Dulay, Burt, and Krashen (1982). This study employed a descriptive qualitative method involving 27 students as the participants. The data were collected through a writing task and analyzed by classifying the errors into omission, addition, misformation, and misordering categories. The findings revealed that a total of 369 errors were identified, consisting of 243 misformation errors, 69 omission errors, 42 addition errors, and 15 misordering errors. Misformation was identified as the most dominant error type, indicating that students continued to experience difficulties in applying correct grammatical forms, particularly in subject–verb agreement and verb usage. This dominance also suggests that students had partially understood sentence structures but lacked grammatical accuracy in constructing descriptive texts. The study concludes that vocational high school students still experience significant challenges in producing grammatically accurate descriptive writing. Therefore, more focused grammar instruction and guided writing practice are needed to improve students’ writing skills.